Popularity Comparison between E-Commerce and Traditional Retail Business - Dulce Jimenez; Sade Valdes; Mariana Salinas (International Journal of Technology for Business (IJTB), 2019)
People around the world are becoming increasingly busy with their lifestyle and are looking for the fastest, easiest and cheapest way to complete variety of our routine tasks. Because of this phenomenon, the traditional retailers have become an unfriendly alternative for a part of the population for a variety of purchases. The main benefit of e-commerce is that people can purchase wherever they are, without having to leave home, and finding everything they need just by typing a couple of words. This paper investigates the importance of e-commerce in the daily lives of people. In order to do so the paper conducted an analysis of secondary data sources and have undertaken a sample survey. It should be noted that the research is in the global context and survey participants are from various countries in Europe, Americas and Asia. The findings of this research suggest that consumers are still sceptic regarding accurate delivery of products purchased online; suitability of payment methods; and the use of personal data harvested by the online retailers.
Keywords: 650; E-Commerce; Consumer Behaviour; Retail; Survey; Online Purchase